2017
DOI: 10.3390/plants6010006
|View full text |Cite
|
Sign up to set email alerts
|

Heat Stress Decreases Levels of Nutrient-Uptake and -Assimilation Proteins in Tomato Roots

Abstract: Global warming will increase root heat stress, which is already common under certain conditions. Effects of heat stress on root nutrient uptake have rarely been examined in intact plants, but the limited results indicate that heat stress will decrease it; no studies have examined heat-stress effects on the concentration of nutrient-uptake proteins. We grew Solanum lycopersicum (tomato) at 25 °C/20 °C (day/night) and then transferred some plants for six days to 35 °C /30 °C (moderate heat) or 42 °C/37 °C (sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
97
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(136 citation statements)
references
References 39 publications
(66 reference statements)
7
97
0
7
Order By: Relevance
“…S1) suggests the diminishing of antagonistic interactions ( i.e ., Zn‐P and Zn‐Fe antagonisms) by supra‐optimal growth temperature. In line with our findings, chronic or abrupt heat stress commonly reduced shoot mineral nutrient concentrations in many other crop species due to a range of physiological and morphological disorders including reduced root growth, synthesis and root‐to‐shoot transport of plant hormones, disrupted source‐sink relations, decreased levels of nutrient‐uptake and ‐assimilation proteins or direct damage of heat on root cells ( Huang et al., ; Heckathorn et al., ; Giri et al., ).…”
Section: Discussionsupporting
confidence: 89%
“…S1) suggests the diminishing of antagonistic interactions ( i.e ., Zn‐P and Zn‐Fe antagonisms) by supra‐optimal growth temperature. In line with our findings, chronic or abrupt heat stress commonly reduced shoot mineral nutrient concentrations in many other crop species due to a range of physiological and morphological disorders including reduced root growth, synthesis and root‐to‐shoot transport of plant hormones, disrupted source‐sink relations, decreased levels of nutrient‐uptake and ‐assimilation proteins or direct damage of heat on root cells ( Huang et al., ; Heckathorn et al., ; Giri et al., ).…”
Section: Discussionsupporting
confidence: 89%
“…A significant reduction in vital minerals such as K, Ca, Fe, P, Mn, and Zn was noticed with in heat and/or drought‐stressed lentil plants, which might be attributed to reduction in root biomass and number in case of heat stress (Giri, Heckathorn, Mishra, & Krause, ), and impaired trasnpiration, stomatal conductance, decreased root function in case of drought stress (Farooq, Wahid, Kobayashi, Fujita, & Basra, ). These impacts intensified in the presence of both the stresses at the same time, which severely decreased the leaf water relations to inhbit the trasnlcoation of minerals into the developing seeds.…”
Section: Discussionmentioning
confidence: 99%
“…As several prior laboratory-based studies showed, the HW effect was first noticed at the cellular level, which resulted in a decrease in photosynthetic enzyme activity and low stomatal conductance and had effects on other eco-physiological characteristics Zinta et al, 2014). Recent findings have confirmed that HWs significantly alter plant photosynthesis and respiration (Qu, Chen, Bunce, Zhu, & Sicher, 2018;Rashid et al, 2018), reduce CO 2 uptake (Tatarinov et al, 2016), and lead to the redistribution of carbon and nitrogen in a plant or community (Birami et al, 2018;Giri, Heckathorn, Mishra, & Krause, 2017). Here, mowing had a similar effect on the community but directly removed plant parts (photosynthetic product) rather than reducing the accumulation rate.…”
Section: Hws and Mowing Prolong Plant Phenologymentioning
confidence: 97%